Development of a zooplankton biotic index for trophic state prediction in tropical reservoirs - De-Carli, Bruno Paes [UNESP]; Bressane, Adriano; Longo, Regina Márcia; Manzi-Decarli, Agatha; Moschini-Carlos, Viviane [UNESP]; Pompêo, Marcelo Luiz Martins (Asociacion Iberica de Limnologia, 2019)
Reservoirs are built mainly for public supply and power generation. However, water quality is almost always compromised by discharge of domestic and industrial sewage, as well as by agricultural residues. Several ecological indices are currently used to analyze different impacts in this environment. The aim of this study was to develop a zooplankton index for tropical reservoirs. Limnological data were obtained from seven Brazilian reservoirs (Atibainha, Broa, Barra Bonita, Salto Grande, Rio Grande, Itupararanga, and Igaratá). Weighted values of ecological optimum were obtained through species response analysis (unimodal distribution) related to chlorophyll a concentration. The results obtained using the zooplankton index (ZBI) proposed had significant correlations with eutrophication indicators. Overall, poor and regular water quality were verified in most reservoirs, partially corroborating the zooplankton community index proposed for Brazilian reservoirs. For further progress, the approach presented here must be tested in other regions. In addition, the ecological indices derived from different aquatic communities should be integrated into a composite index.
Desenvolvimento de um índice biótico do zooplâncton para predição do estado trófico em reservatórios tropicais
Keywords: Ecological potential; Eutrophication; São Paulo State; Zooplanktonic index